2015
DOI: 10.1002/eji.201445215
|View full text |Cite
|
Sign up to set email alerts
|

IMQ‐induced skin inflammation in mice is dependent on IL‐1R1 and MyD88 signaling but independent of the NLRP3 inflammasome

Abstract: Keywords: IL-1R r Imiquimod r MyD88 r NLRP3 inflammasome r Skin inflammation Additional supporting information may be found in the online version of this article at the publisher's web-site Correspondence: Dr. Franck Morel e-mail: f.morel@univ-poitiers.fr IntroductionPsoriasis is a chronic inflammatory skin disease estimated to affect 2-3% of the general population [1]. Clinical presentation is usually associated with red, scaly, and raised plaques. These are the C 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 45 publications
4
48
2
Order By: Relevance
“…It is unclear why the results from Rabeony et al disagree with previously published results demonstrating reduced imiquimod cream-induced skin inflammation in caspase-1-deficient mice, or with our results with CP-456,773 in the present study (47). However, Rabeony et al (48) do demonstrate that IL-1a and IL-1b together contribute to dermatitis and that caspase-1 activity is upregulated in response to imiquimod cream in their model. Furthermore, it has been reported that the isostearic acid component of the imiquimod cream can activate NLRP1 inflammasome-dependent cleavage and release of IL-1b from human keratinocytes and that isostearic acid might contribute to inflammation (49).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…It is unclear why the results from Rabeony et al disagree with previously published results demonstrating reduced imiquimod cream-induced skin inflammation in caspase-1-deficient mice, or with our results with CP-456,773 in the present study (47). However, Rabeony et al (48) do demonstrate that IL-1a and IL-1b together contribute to dermatitis and that caspase-1 activity is upregulated in response to imiquimod cream in their model. Furthermore, it has been reported that the isostearic acid component of the imiquimod cream can activate NLRP1 inflammasome-dependent cleavage and release of IL-1b from human keratinocytes and that isostearic acid might contribute to inflammation (49).…”
Section: Discussioncontrasting
confidence: 98%
“…Reduced skin inflammation and dermal thickness induced by imiquimod cream has been observed in caspase-1-deficient mice (47). However, in a recent publication from Rabeony et al (48), imiquimod cream-induced skin inflammation was not reduced in NLRP3-, caspase-1-, and ASC-deficient mice. It is unclear why the results from Rabeony et al disagree with previously published results demonstrating reduced imiquimod cream-induced skin inflammation in caspase-1-deficient mice, or with our results with CP-456,773 in the present study (47).…”
Section: Discussionmentioning
confidence: 96%
“…This previous study demonstrated that P2X7-mediated IL-1β release, which requires NLRP3 inflammasome activation [36], was essential for allergic contact dermatitis [35]. In contrast, activation of the NLRP3 inflammasome is not required for IMQ-induced psoriasis-like inflammation [37]. Thus, this provides a possible explanation as to why P2X7 is not essential in this model of psoriasis.…”
Section: Discussionmentioning
confidence: 84%
“…Other cytokines such as TNF-α, IL-1α/β, or IL-18 have been involved in the pathogenesis of psoriasis as well [8,9]. The contribution of these cytokines has been mainly studied using the standard mouse model of psoriasis-like skin inflammation induced by topical application of imiquimod (IMQ) [10][11][12][13]. Oncostatin M (OSM) has also been reported to be overexpressed in skin lesions of patients with psoriasis and shown to have proinflammatory activities in vitro on human primary keratinocytes and reconstituted epidermis [14].…”
Section: Introductionmentioning
confidence: 99%